Meneroka Perspektif Menangani Ektremisme di Malaysia Melalui Pendekatan Naratif Alternatif Digital - Kartini Kamaruzzaman; Ros Aiza Mohd Mokhtar; Abdul Rashid Abdul Aziz; Ali Nasser Ali Al-tahitah; Is’haq Ibrahim Ahmad Bani Melhem (SecholianPublication, 2024)
VOL 8 NO 9